RFID application system in checking patient - Nor'aqilah, Misman (2011)
In this research, I will focus on the software design and database system model for kiI[)Application System in Checking Patient. This system builds to replace the manual process to register patient information and avoid medical mistake. The previous manual process had caused a lot of troubles and not systematic.IT is developed to provide a digitizing form to help the administrator to perform their task in a more efficient way and also to avoid mistake in checking patients especially in ward. Based on the system,it provides data availability for read operations while supporting fault tolerance and fast data transformation. Accurate,relevant and timely information required the use of sophisticated system, with the database management system,with using Microsoft Access.